High‐resolution simulation of the boreal summer intraseasonal oscillation in Met Office Unified Model. (7th December 2016) - Fang, Yongjie; Wu, Peili; Mizielinski, M. S.; Roberts, M. J.; Wu, Tongwen; Li, Bo; Vidale, Pier Luigi; Demory, Marie‐Estelle; Schiemann, Reinhard
Abstract : The present study investigates the fidelity and resolution sensitivity of Met Office Unified Model Global Atmosphere 3.0 in simulating the intraseasonal oscillation (ISO) of the East Asia and western North Pacific summer monsoon. Two sets of model simulations at horizontal resolutions of N216 (60 km) and N96 (130 km) forced by observed daily high‐resolution sea‐surface temperature are examined and compared with the observations. Diagnostic results show that the model can well reproduce the gross spatio‐temporal features of observed summer ISO over East Asia and the western North Pacific in terms of period, dominant rotated empirical orthogonal function (REOF) mode, variance, northward propagation, cycle evolution and vertical structure. The intraseasonal change in intensity and position of the western North Pacific subtropical high and upper troposphere westerly jet associated with the northward propagating ISOs are also reasonably captured in the model. Moreover, increasing horizontal resolution improves most aspects of the ISO simulation, especially the intensity and northward propagation of the ISO‐related convection and circulation systems. Further analysis indicates that the improvement as resolution increases is related to the weakening in background state of the East Asian summer monsoon, which is due to the realistic simulation of land–sea thermal contrast in the higher resolution model. This study suggests that enhanced model resolution can have some beneficial impacts on the ISO simulation.